PENGARUH DIGITAL MARKETING DAN KUALITAS PRODUK TERHADAP MINAT BELI DI OI KAFE SURABAYA - Abdilah, Fikri Rizki; Winarno, Sri Tjondro; Wijayati, Prasmita Dian (International Journal of Multidisciplinary Research and Literature, 2024)
This study was conducted with the aim of analyzing the effect of digital marketing on product purchase intention at Oi Kafe and to analyze the effect of product quality on product purchase intention at Oi Kafe. The data analysis used in this study used SEM-PLS analysis with the WarpPLS approach. The use of the PLS method as an analysis technique has the advantage that the sample used does not have to be large and can be used in developing a theory. The results of this study indicate that digital marketing has a positive and significant effect on purchase intention at Oi Kafe. The Oi Kafe Instagram content provided is informative. Consumers feel attracted to content with an attractive design and appearance on Oi Kafe's Instagram. Product quality has a positive and significant effect on buying interest in Oi Kafe. Consumers feel interested in making purchases with the attractive packaging offered which increases the durability of coffee products